Facilitating class attendance to improve student achievements - Sun, Ye; Chen, Weifeng (Teaching Mathematics and Computer Science, 2011)
Many studies have revealed that attendance is strongly associated with students’ achievements, and have proposed different strategies to improve students’ attendance. However, there are few studies investigating how to efficiently take students’ attendance – the key component to improve students’ attendance. Taking attendance manually is inefficient since it will consume part of the limited class time. This paper describes the design and the implementation of an online attendance system that is currently used in classes at West Virginia University and California University of Pennsylvania. Examples of the system are provided online. Implementation codes of the system are shared, which can be used to teach computer science courses such as Web Programming or Client-Server Script Languages.